Tumor markers: a proteomic approach - Abrishamkar, Afshin; Heidari Keshel, Saeed; Rahnema Falavarjani, Eiman; Ebrahimi, Maryam; Raeisossadati, Reza; Roozafzoon, Reza; Behrouzi, Gholam Reza (Archives of Advances in Biosciences, 2013)
This article reviews the recently published data on the diagnosis of cancer with proteomics, including the major proteomics technologies and promising strategies for biomarker discovery and development. Most of the tumor markers are proteins that either numerically increase in response to the alteration of cancer conditions or are produced by cancer cells. However, they are natural compounds ordinarily available in the typical cells to a little extent what are affected by increase of expression due to cancer and its intensity in blood, body fluids or tissues. Tumor markers are substances normally available in body fluids such as serum, urine, blood, and tissues that increase in the desired tissue of cancer patients. Most of tumor markers are proteins that either are produced in response to changes in cancer conditions or are made by the cancer cells. However, most of tumor markers are among the natural compounds of normal cells present in normal conditions in the cell in small amounts and are affected by increase of expression, due to cancer and their levels in the blood, body fluids or tissues.